PENGARUH CARBON EMISSION DISCLOSURE, UKURAN PERUSAHAAN DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - Widi Putri Matalata; Lilik Pirmaningsih; Fadilla Purwitasari (Jurnal Ilmiah Akuntansi, 2025)
This study aims to determine the effect of carbon emission disclosure, firm size, and environmental performance on firm value in mining companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023. This research employs a quantitative approach using secondary data obtained from annual reports, sustainability reports, and PROPER ratings. A total of 52 observations from 13 purposively selected companies were analyzed using multiple linear regression with SPSS. The results indicate that, simultaneously, the three independent variables have a significant effect on firm value. However, when tested partially, carbon emission disclosure and environmental performance do not show a significant effect, while firm size has a positive effect on firm value.